The Role of TikTok in Influencing Generation Z's Decision in the 2024 Election - Arrizal, Faturachman; Indah Wenerdha (Jogjakarta Communication Conference (JCC), 2024)
The 2024 general election in Indonesia has attracted the attention and enthusiasm of the public to participate in the democratic party process. As the next generation of the nation, Generation Z must actively contribute to politics. This generation was born in a technology-savvy era with the most active social media usage intensity in the world. The problem that occurs is that Generation Z is currently faced with a very complicated and dynamic political reality. The spread of hoax information and political identity are factors of concern for young people, who are vulnerable to being influenced. This research aims to find out the opinions of Generation Z as TikTok social media users about the political reality of young people, which is being discussed in Rian Fahardhi's TikTok video entitled Meta Prabowo-Gibran. It is important to know how Generation Z views political reality on social media in terms of voting decisions. Using a qualitative approach method that explains phenomena in depth, reception analysis is used to explore the awareness of sources in receiving and understanding objects. Data collection techniques use interviews, the internet, and literature studies to obtain a theoretical basis for the problem to be studied. Stuart Hall's encoding and decoding model was used to categorize the speakers into three groups: dominant position, oppositional position, and negotiated position. The results show that the majority of Generation Z is interested in discussing political issues. Branding on social media and presidential and vice presidential debate sessions are their main concerns in choosing. The violations that occurred at the Constitutional Court still generated a lot of controversy over the vice presidential nomination. This happened because of the source's partiality towards his choice. The track record of young people in achieving political positions today is still doubtful because many use popularity and family support.